2023
DOI: 10.22270/ujpr.v7i6.862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Removable Dentures on Colonization of Aerobic Bacteria in the Oral Cavity and Antibiotic Pattern of the Common Isolated Bacteria

Abstract: Background and aims: Wearing a removable dental prosthesis causes a change in the micro flora of the mouth. The aim of this research was to verify the composition of aerobic bacterial in the oral cavity of patients with removable dentures and with normal teeth (without dentures), and antibiotics pattern for common isolates. Methods: Bacteriological investigations were performed in 122 individuals (61 removable dentures: 61 normal teeth) attending dental clinics of Faculty of dentistry, Sana’a University, Yemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…After positioning the implant fixture to maximize osseointegration, a dental prosthesis is affixed. Before the dental prosthetic (a tooth, bridge, or denture) is affixed to the implant or an abutment is positioned to support a dental prosthetic/crown, osseointegration must take a varied period of healing time [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After positioning the implant fixture to maximize osseointegration, a dental prosthesis is affixed. Before the dental prosthetic (a tooth, bridge, or denture) is affixed to the implant or an abutment is positioned to support a dental prosthetic/crown, osseointegration must take a varied period of healing time [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that during the healing period needed for osseointegration, there was a variable degree of change in the oral conditions, such as changes in the colonization of oral microorganisms and oral s-IgA level, before either the dental prosthetic (a tooth, bridge, or denture) is attached to the implant or an abutment is placed to hold a dental prosthetic/crown [16,17]. Implant success or failure is largely determined by the thickness and condition of the bone and gingival tissues surrounding the implant, as well as by factors such as serum immunoglobulin A (sIgA), gingival sulcus cytokines, oral microbial balance, patient health, and medications that alter the likelihood of osseointegration [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It also caused oral infections. Acute dentoalveolar abscess, dry mouth, denture wearers, and angular chelitis [29][30][31][32][33] , among other oro-facial illnesses, have also been linked to S. aureus in the oral cavity has been linked to systemic infections and potentially fatal conditions include aspiration pneumonia, rheumatoid arthritis, and infective endocarditis 23,34-36 . When there are more colonization in oral cavity, there is a higher chance of infections, which can change oral and overall health issues.…”
Section: Introductionmentioning
confidence: 99%